PENGARUH LIKUIDITAS, SALES GROWTH, LEVERAGE, DAN FIRM SIZE TERHADAP KINERJA KEUANGAN - Nayottama, Azhar Prasetyo; Dewi, Sofia Prima (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to find out how the influence of Liquidity, Sales Growth, Leverage, and Firm Size on financial performance in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2021. The sampling method used purposive sampling. The sample in this study was 340 data from 68 companies for five years. The data processing technique uses multiple regression analysis assisted by the E-views 9 program. The results of this study prove that leverage has a negative effect on financial performance, sales growth does not have a positive effect on financial performance, while liquidity and firm size do not negatively affect financial performance.